In vitro Activity of Pentamidine Alone and in Combination With Aminoglycosides, Tigecycline, Rifampicin, and Doripenem Against Clinical Strains of Carbapenemase-Producing and/or Colistin-Resistant Enterobacteriaceae - Cebrero-Cangueiro, Tania; Álvarez-Marín, Rocío; Labrador-Herrera, Gema; Smani, Younes; Cordero-Matía, Elisa; Pachón, Jerónimo; Pachón-Ibáñez, María Eugenia (Frontiers in Cellular and Infection Microbiology, 2018)
Enterobacteriaceae cause different types of community- and hospital-acquired infections. Moreover, the spread of multidrug-resistant Enterobacteriaceae is a public health problem and the World Health Organization pointed them among the pathogens in which the search of new antibiotics is critical. The objective of this study was to analyze the in vitro activity of pentamidine alone and in combination with gentamicin, tobramycin, amikacin, tigecycline, rifampicin, or doripenem against eight clinical strains of carbapenemase-producing and/or colistin-resistant Enterobacteriaceae: five carbapenemase-producing Klebsiella pneumoniae, one carbapenemase-producing Escherichia coli, and two colistin-resistant Enterobacter cloacae. MIC and MBC were determined following standard protocols. MIC results were interpreted for all the antibiotics according to the EUCAST breakpoints but for rifampicin in which the French FSM breakpoint was used. Bactericidal and synergistic activity of pentamidine alone and in combination with antibiotics at concentrations of 1xMIC was measured by time-kill curves. For one selected strain, K. pneumoniae OXA-48/CTX-M-15 time-kill curves were performed also at 1/2xMIC of pentamidine. All studies were performed in triplicate. Pentamidine MIC range was 200–800 μg/mL. The 50, 12.5, 62.5, 87.5, and 62.5% of the strains were susceptible to gentamicin, tobramycin, amikacin, tigecycline, and doripenem, respectively. Only the two E. cloacae strains were susceptible to rifampicin. Pentamidine alone at 1xMIC showed bactericidal activity against all strains, except for the E. cloacae 32 strain. The bactericidal activity of pentamidine alone was also observed in combination. The combinations of pentamidine were synergistic against E. cloacae 32 with amikacin and tobramycin at 24 h and with tigecycline at 8 h. Pentamidine plus rifampicin was the combination that showed synergistic activity against more strains (five out of eight). Pentamidine plus doripenem did not show synergy against any strain. At 1/2xMIC, pentamidine was synergistic with all the studied combinations against the K. pneumoniae OXA-48/CTX-M-15 strain. In summary, pentamidine alone and in combination shows in vitro activity against carbapenemase-producing and/or colistin-resistant Enterobacteriaceae. Pentamidine appears to be a promising option to treat infections caused by these pathogens.